Immunogenicity and safety of the 15-valent pneumococcal conjugate vaccine, a systematic review and meta-analysis - Gernot Wagner; Gerald Gartlehner; Kylie Thaler; Dominic Ledinger; Johanna Feyertag; Irma Klerings; KM Saif-Ur-Rahman; Declan Devane; Kate Olsson; Karam Adel Ali; Sabine Vygen-Bonnet; Heini Salo; et al. (npj Vaccines)
Abstract Pneumococcal infections are a serious health issue associated with increased morbidity and mortality. This systematic review evaluated the efficacy, effectiveness, immunogenicity, and safety of the pneumococcal conjugate vaccine (PCV)15 compared to other pneumococcal vaccines or no vaccination in children and adults. We identified 20 randomized controlled trials (RCTs). A meta-analysis of six RCTs in infants showed that PCV15 was non-inferior compared with PCV13 for 12 shared serotypes. Based on a meta-analysis of seven RCTs in adults, PCV15 was non-inferior to PCV13 for 13 shared serotypes. For the unique PCV15 serotypes, 22F and 33F, immune responses were higher in infants and adults vaccinated with PCV15 compared to those receiving PCV13. Regarding safety, meta-analyses indicated comparable risks of adverse events between PCV15 and PCV13 in infants. Adults receiving PCV15 had a slightly higher risk of adverse events, though serious events were similar between groups.